Pengaruh CR dan EPS Terhadap Return Saham Perusahaan JII70 Periode 2019-2024 - zaneta daniftria; Ratna Juwita (Universitas Multi Data Palembang, 2026)
This study aims to determine the effect of Current Ratio (CR) and Earning per Share (EPS) on Stock Returns of Companie on IDX JII70 listed on the Indonesia Stock Exchange (IDX) for the period 2019-2024. In this study, the research method used is a quantitative research method. The population of this study is the Company on IDX JII70 listed on the Indonesia Stock Exchange (IDX) from 2019 - 2024. The sample in this study was obtained using a purposive sampling technique totaling 26 company on IDX JII70. The data analysis technique used in this study is multiple linear regression. The results of the study indicate that CR has a positive and significant effect on Stock Return and EPS has a positive and significant effect on Stock Return. CR and EPS simultaneously and significantly influence stock return.